Adhesion Promotes Allergic Rhinitis CD4+IL4+ T Cell Differentiation via ICAM1 and E-Selectin. Issue 4 (July 2022) - Liu, Honghui; Ai, Jingang; Wang, Tiansheng; Tan, Guolin
Background: Neuroimmune communication plays an important role in allergic inflammation, but the neuroimmune regulation of allergic rhinitis remains unclear. Objective: The goal of this study was to investigate the role of CD4-positive T lymphocyte (CD4 + T cells) adhesion to D-U87 neuron-like cells in mediating allergic rhinitis CD4 + T cell differentiation. Methods: D-U87 neuron-like cells were derived from the human glioblastoma U87 cell line. CD4 + T cells were isolated from human peripheral blood using a magnetic separation technique. In vitro coculture of D-U87 neuron-like cells and CD4 + T cells was established. The number of adherent CD4 + T cells was counted using a fluorescence microscope. The percentages of CD4 + IFNγ + and CD4 + IL4 + T cells and the levels of IFNγ and IL4 cytokines in the supernatant were measured by flow cytometry. Results: The results showed that the number of adherent CD4 + T cells in patients with allergic rhinitis was significantly higher than that in healthy controls. In allergic rhinitis, the percentage of CD4 + IL4 + T cells was significantly increased in the adherent group compared with that in the nonadherent group. Moreover, blocking ICAM1 and E-selectin decreased the number of adherent CD4 + T cells and the percentage of CD4 + IL4 + T cells in allergic rhinitis. Conclusion: Adhesion contributes to CD4 + IL4 + T cell differentiation in the in vitro coculture system of D-U87 neuron-like cells and allergic rhinitis CD4 + T cells, which may provide new insights into therapeutic strategies for allergic rhinitis.